Динаміка рівнів імунозапальних маркерів на тлі терапії кверцетином у хворих на ішемічну хворобу серця, асоційовану з гіпотиреозом - Михайловська, Наталія Сергіївна; Олійник, Тетяна Вікторівна (My University, 2016)
Досліджено динаміку рівнів імунозапальних маркерів у хворих на ішемічну хворобу серця, асоційовану з гіпотиреозом, на тлі терапії кверцетином. Встановлено, що кверцетин у комплексному лікуванні хворих на ішемічну хворобу серця з супутнім гіпотиреозом впродовж 3 місяців поліпшує функціональний стан ендотелію та знижує активацію системного запального процесу. The hypothyroidism in patients with ischemic heart disease favors its progression. The aim of research was to study the dynamics of immunoinflammatory markers level in patients with ischemic heart disease associated with hypothyroidism on the background of quercetin therapy. Methods of research. 23 patients with ischemic heart disease: the stable exertion angina of I-III functional class with concomitant hypothyroidism took part in research. 13 patients underwent the standard basic therapy of ischemic heart disease and hypothyroidism; 10 patients received quercetin as an additional preparation to the main therapy. Using ummunosorbent method there were detected the level of alpha-tumor necrosis factor, C-reactive protein, endotelin-1, tissue activator inhibitor plasminogen-1, neopterin; using immunochemiluminiscent method there was detected the levels of thyrotropic hormone and Т4 free one. Results. Under the influence of basic therapy including quercetin there was noticed the reliable decrease of endotelin-1 and alpha-tumor necrosis factor, was detected the tendentious decrease of tissue activator inhibitor plasminogen-1, C-reactive protein and neopterin in 3 month of treatment. Conclusions. Basic therapy with quercetin as an additional preparation has a normalizing influence on the systemic inflammatory process and endothelial dysfunction and that grounds the expediency of the use of this complex pharmacotherapy in patients with ischemic heart disease associated with hypothyroidism.
Dynamics of immunoinflammatory markers level on the background of quercetin therapy in patients with ischemic heart disease associated with hypothyroidism
Keywords: імунозапальні маркери; ішемічна хвороба серця; гіпотиреоз; кверцетин; immunonflammatory markers; ischemic heart disease; hypothyroidism; quercetin